The effect of sugars on amino-acid transport - Saunders, Stuart (Department of Medicine, 2020)
At the turn of this century the form in which ingested protein was absorbed from the intestine was unknown. Voit had postulated in 1867 that protein was absorbed as such, and passed through the blood to the tissues, where it was oatabolised without becoming part of the "living protoplasm". This concept implied that "circulating protein" was in solution, that protein catabolim could take place only in that state, and that when living protoplasm "died", it was first dissolved, and subsequently became part of the circulating protein derived from the food.